Nannochloropsis sp phytoplankton culture technique laboratory scale - Hidayat, Nurul; Putri, Mega Novia; Kurniawan, Ronal (Science, Technology, and Education Care, 2024)
Nannochloropsis sp is a phytoplankton often used in marine fish hatchery activities as feed for the mass production of rotifers, and its availability is very much needed for rearing marine fish larvae. This activity aims to study pure culture techniques for Nannochloropsis sp on a laboratory scale. The method used is a literature study method and a direct practical method regarding Nannochloropsis sp phytoplankton culture techniques laboratory scale and conducted interviews with employees at the BPBL Batam Phytoplankton Live Food Production Unit Laboratory. Based on observations, it was found that the peak growth or optimum cell density of Nannochloropsis sp. occurred on the sixth day in a 1000 mL Erlenmeyer, namely 60.95 - 62.10 million cells/mL with an initial density of 10.15 - 10.55 million cells/mL and in a 2000 mL Erlenmeyer, namely 58.75 - 60, 25 million cells/mL with an initial density of 8.25 – 8.45 million cells/mL.